2013
DOI: 10.4314/sokjvs.v11i2.5
|View full text |Cite
|
Sign up to set email alerts
|

Haematogical changes induced by subchronic glyphosate exposure: Ameliorative effect of zinc in Wistar rats

Abstract: The aim of this study was to determine the haematological changes induced by subchronic glyphosate exposure in Wistar rats and the ameliorative effect of zinc. Sixty adult male and female Wistar rats were used for the study. Twelve of them were used for the LD 50 which was evaluated to be 3750 mg kg-1 with clinical signs of respiratory distress, diarrhoea, rough hair coat and subsequently death observed. The remaining 48 rats were divided into six groups of four males and four females each. The agent(s) admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
2
8
0
Order By: Relevance
“…The co-treatment of Cu intoxicated rats with N-Zn and/ or Zn corrected the anemia induced by cu by restoring RBCs count, Hb concentration, MCV, MCHC and platelets count to normal levels. This agreed with Tizhe et al (2013) who reported that Zn modulated the parameters of anemia induced by an herbicide glyphosate. This could be attributed to that Zn serves as a cofactor of many enzymes and has antioxidant effects (Powell, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…The co-treatment of Cu intoxicated rats with N-Zn and/ or Zn corrected the anemia induced by cu by restoring RBCs count, Hb concentration, MCV, MCHC and platelets count to normal levels. This agreed with Tizhe et al (2013) who reported that Zn modulated the parameters of anemia induced by an herbicide glyphosate. This could be attributed to that Zn serves as a cofactor of many enzymes and has antioxidant effects (Powell, 2000).…”
Section: Discussionsupporting
confidence: 81%
“…Group III (G1) rats were administered glyphosate orally at 14.4 mg/kg body weight (low dose, <1% LD 50 ). 24 …”
Section: Methodsmentioning
confidence: 99%
“…24 Group IV (G2) rats were administered glyphosate orally at 375 mg/kg body weight (10% LD 50 ). 24 Group V (G3) rats were administered glyphosate at 750 mg/kg body weight (20% LD 50 ). 24 Group VI (ZG1) rats were pretreated with zinc chloride (50 mg/kg) and then administered glyphosate at 14.4 mg/kg body weight 1 hour later.…”
Section: Chronic Toxicity Studymentioning
confidence: 99%
“…Group IV (G2) received 375 mg/kg of the glyphosate-based herbicide Bushfire V R (10% of the half-maximal lethal dose [LD 50 ]). 21 Group V (G3) received 750 mg/kg Bushfire V R (20% of the LD 50 ). 21 Group VI (ZG1) was pretreated with zinc (50 mg/kg) and then administered Bushfire V R (14.4 mg/ kg) 1 hour later.…”
Section: Chronic Toxicity Studymentioning
confidence: 99%
“…21 Group V (G3) received 750 mg/kg Bushfire V R (20% of the LD 50 ). 21 Group VI (ZG1) was pretreated with zinc (50 mg/kg) and then administered Bushfire V R (14.4 mg/ kg) 1 hour later. Group VII (ZG2) was pretreated with zinc (50 mg/kg) and then administered Bushfire V R (375 mg/kg) 1 hour later.…”
Section: Chronic Toxicity Studymentioning
confidence: 99%